Pengaruh Permainan Memancing Terhadap Kemampuan Mengenal Lambang Bilangan Anak Usia 5-6 Tahun Di Tk Permata Hati Hutagalung (Sekolah Tinggi Agama Buddha Nalanda, 2023)
The aim of this research is to determine the Influence of Fishing Game on the Ability to Recognize Number Symbols in 5-6-Year-Old Children at Permata Hati Hutagalung Kindergarten. The research method used is a quantitative descriptive and inferential method. The population consists of 30 children aged 5-6 years at Permata Hati Hutagalung Kindergarten, and the entire population is used as respondents in the study. Data was collected using a closed positive questionnaire with 30 items, 15 for variable X and 15 for variable Y. The data analysis results indicate that there is an Influence of the Fishing Game on the Ability to Recognize Number Symbols in 5-6-Year-Old Children at Permata Hati Hutagalung Kindergarten: 1) Analysis of requirements: a) The test for a positive relationship obtained a value of rxy = 0.473, which is greater than the table value (α=0.05, n=30) = 0.361. b) The test for a significant relationship obtained a calculated t-value of 2.042, which is greater than the table value (α=0.05, df=n-2=28) = 2.048. 2) Influence test: a) Regression equation test resulted in the regression equation Y ̂=